2013
DOI: 10.1063/1.4789681
|View full text |Cite
|
Sign up to set email alerts
|

Impacting university physics students through participation in informal science

Abstract: Informal education programs organized by university physics departments are a popular means of reaching out to communities and satisfying grant requirements. The outcomes of these programs are often described in terms of broader impacts on the community. Comparatively little attention, however, has been paid to the influence of such programs on those students facilitating the informal science programs. Through Partnerships for Informal Science Education in the Community (PISEC) at the University of Colorado Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…Prior work shows that outcomes for physicists who participate in informal physics programs are improved scientific communication skills [3] and gaining teaching experience [4]. Additional research in chemistry [5] indicates that another way engaging in outreach activities benefits academics is by reinforcing their excitement about science.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work shows that outcomes for physicists who participate in informal physics programs are improved scientific communication skills [3] and gaining teaching experience [4]. Additional research in chemistry [5] indicates that another way engaging in outreach activities benefits academics is by reinforcing their excitement about science.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we will briefly describe some of the early work on which our current work builds. Through studying the Partnerships for Informal Science Education in the Community (PISEC) initiative at the University of Colorado Boulder, researchers found that student facilitators of an after school mentoring program experienced positive shifts in their perspectives of teaching and learning, and improved their science communication skills [11,12]. Recent work from Fracchiolla et al characterizing the experiences of two graduate physics students through a community of practice framework has suggested that facilitating informal physics programs may have a positive influence on the development of a student's physics identity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other potentially related factors such as underdeveloped physics self-identity, low self-efficacy, and low motivation can negatively influence female student success and retention [8][9][10][11][12][13][14][15][16]. A vast majority of prior studies seeking to improve female student representation and retention in physics concentrated on student experiences in formal physics settings such as classrooms and labs while the impact of informal physics programs on student development as a physicist has been often overlooked [17,18].…”
Section: Introductionmentioning
confidence: 99%